Immune Responses to Tissue-Restricted Nonmajor Histocompatibility Complex Antigens in Allograft Rejection. (9th January 2017) - Bharat, Ankit; Mohanakumar, T.
Abstract : Chronic diseases that result in end-stage organ damage cause inflammation, which can reveal sequestered self-antigens (SAgs) in that organ and trigger autoimmunity. The thymus gland deletes self-reactive T-cells against ubiquitously expressed SAgs, while regulatory mechanisms in the periphery control immune responses to tissue-restricted SAgs. It is now established that T-cells reactive to SAgs present in certain organs (e.g., lungs, pancreas, and intestine) are incompletely eliminated, and the dysregulation of peripheral immuneregulation can generate immune responses to SAgs. Therefore, chronic diseases can activate self-reactive lymphocytes, inducing tissue-restricted autoimmunity. During organ transplantation, donor lymphocytes are tested against recipient serum (i.e., cross-matching) to detect antibodies (Abs) against donor human leukocyte antigens, which has been shown to reduce Ab-mediated hyperacute rejection. However, primary allograft dysfunction and rejection still occur frequently. Because donor lymphocytes do not express tissue-restricted SAgs, preexisting Abs against SAgs are undetectable during conventional cross-matching. Preexisting and de novo immune responses to tissue-restricted SAgs (i.e., autoimmunity) play a major role in rejection. In this review, we discuss the evidence that supports autoimmunity as a contributor to rejection. Testing for preexisting and de novo immune responses to tissue-restricted SAgs and treatment based on immune responses after organ transplantation may improve short- and long-term outcomes after transplantation.